Epidemiologia da leptospirose em mamíferos silvestres de vida livre da região de Botucatu, SP - Fornazari, Felipe [UNESP] (2015)
Leptospirosis is considered a zoonoses of great importance in animals and humans. Due to the lack of studies in wild animals, the present study aimed to investigate the epidemiology of leptospirosis in free-ranging wild mammals from Botucatu, SP. Blood and urine samples were collected from 309 animals, distributes in 16 species. Leptospirosis diagnosis was performed by Microscopic Agglutination Test (MAT) and Real Time PCR (qPCR). Correlations between positivity, clinical disorders and origin of animals were assessed. Sixty-four (20.7%) animals were positive, with higher prevalence among the following species: lesser grisson (83.3%), crab-eating fox (75%), maned wolf (66.6%) and coatis (30.3%). Semaranga serogroup was the most prevalent, especially in opossums. No positive association was observed between diagnosis and clinical disorders. Opossums from forests presented higher chances of infection than those from urban areas (Odds Ratio = 3.87). The results demonstrated the high diversity of wild mammals infected by Leptospira spp. in Botucatu; there are significant differences in the prevalence of infection between species, with higher positivity in Canidae and Mustelidae families; leptospirosis presented low morbidity in the studied animals; opossums presented high prevalence of infection by saprophyte leptospires; and environmental features are involved in the higher prevalence of infection in opossums from the forest than those from urban areas